The Process of Learning English Speaking Skills in Nursing Class - Pebriano, Nor Angga; Rafidiyah, Dina; Sarmila, Sarmila; Murtiningsih, Tenny; Fauziah, Nita; Farhan, Miftah Al; Wariyatun, Wariyatun; Ifani, Muhammad Zulfi; Pradana, Fajar Gemilang (Jurnal Keilmuan dan Keislaman, 2023)
Learning English for nurses is very important because there are many English terms that nurses must know. In addition, for career needs it is also necessary that someone can speak English. Therefore, learning English for nursing is important. This research was case study in qualitative research. its assumed that this study aims to find out the way nursing students learn speaking skills. This research was conducted at a private university in South Kalimantan. In the English class of students majoring in nursing class of 2021, The findings from this study used interviews with two nursing students and one English lecturer who taught nursing classes. The results found that the process of students learning English was quite diverse. because by mastering a foreign language when they carry out their duties as medical personnel they have no difficulty communicating. It can be concluded that the way students learn speaking for the nursing profession is quite diverse, some use strategies through the habit of watching English films, some use materials from lecturers to improve their speaking skills.